Analisis Pola Asuh Demokratis Orang Tua Terhadap Pilihan Makan Anak Studi Kualitatif Anak Usia 4 Tahun Di TK Tadika Puri Pondok Gede - Meiwa Valentina; Sri Watini; Lia Kurniawaty (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The growth and development of young children are significantly influenced by their nutritional intake. Parents play an essential role in ensuring children receive sufficient nutrition for optimal development. Meeting these nutritional needs can be achieved by providing healthy, varied, nutritious, balanced, and safe foods. This study focuses on analyzing democratic parenting patterns toward the eating choices of 4-year-old children at Tadika Puri Kindergarten Pondok Gede. The study employs a qualitative phenomenological approach, using observation, interviews, and documentation. The findings reveal two dominant parenting styles: democratic and permissive. Democratic parenting encourages independence in food choices while maintaining parental guidance and boundaries, whereas permissive parenting tends to grant freedom with minimal control. Both approaches significantly influence the eating preferences and habits of 4-year-old children at Tadika Puri Kindergarten Pondok Gede.